Rose culture - Parks, Lucy Junie (My University, 1898)
Introduction: The rose is a shrub, or dwarf tree, which has beautiful fragrant flowers and is usually protected by thorns. It stands at the head of the floral kingdom, and is called “The Queen of Flowers.” It belongs to the order Rosacea, which includes most of our fruit trees and some of our berries, such as the apple, peach, pear, plum, raspberry, strawberry, blackberry, and many ornamental shrubs. Little is known of the history of the rose. It is mentioned in the early literature, and is thought to have been known to the primitive Egyptians, as several varieties are found in Egypt now. We know that they were cultivated by the Jews during the reign of Solomon, because it is mentioned in the Song of Solomon, It is also mentioned in the Book of Ecclesiastics, the author of which lived seven hundred years after Solomon. Homer speaks of it in his Iliad and his Odyssey. Chancer, who wrote in the thirteenth century who mentions the rose. We find accounts of its origin in more ancient writings.
Citation: Parks, Lucy Junie. Rose culture. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Rose; Ancient Writings; Rosacea; Egyptian; Solomon; Theses; Manuscripts (documents)